ACACA depletion activates the cPLA2–arachidonic acid–NF-κB axis to drive inflammatory reprogramming in androgen receptor-independent prostate cancer - Shaoyou Liu; Yupeng Chen; Jian Chen; Jinchuang Li; Zhenguo Liang; Xinyue Mei; Yuanfa Feng; Zhaodong Han; Funeng Jiang; Yongding Wu; Huijing Tan; Hongwei Luo; et al. (Cell Communication and Signaling)
Abstract Background Acetyl-CoA carboxylase alpha (ACACA) is a key enzyme in fatty acid biosynthesis and a proposed therapeutic target in prostate cancer. However, its role in androgen receptor-independent prostate cancer (ARIPC), an aggressive and treatment-resistant subtype, remains unclear. This study aimed to investigate the effects of ACACA depletion on ARIPC, with a focus on inflammation and metastasis. Methods ACACA expression patterns were analyzed across multiple metastatic castration-resistant prostate cancer (mCRPC) datasets. In ARIPC cell lines, ACACA was inhibited via both shRNA and the pharmacological inhibitor TOFA. Transcriptomic, metabolomic, and single-cell RNA sequencing data were used to identify downstream changes. Inflammatory signaling was assessed by qPCR, western blotting, and immunofluorescence. Cell migration was evaluated via wound healing and transwell assays, and the metastatic potential was examined in a mouse tail vein injection model. The roles of arachidonic acid (AA), cytosolic phospholipase A2 (cPLA2), and NF-κB signaling were further tested through targeted inhibition. Results ACACA expression was reduced in ARIPC and was negatively correlated with inflammatory pathways. Its inhibition upregulated proinflammatory cytokines and chemokines, elevated AA and eicosanoid levels, and increased cPLA2 expression. Single-cell RNA sequencing confirmed NF-κB signaling enrichment in ACACA-low tumor cells. Mechanistically, elevated AA activated NF-κB signaling. ACACA depletion enhanced cell migration and metastasis, along with macrophage infiltration. Inhibiting cPLA2 or NF-κB signaling reversed these effects. Conclusions This study reveals a previously unrecognized tumor-promoting effect of ACACA depletion in ARIPC. Targeting ACACA in this context enhances inflammation and metastasis via arachidonic acid-mediated activation of NF-κB signaling. These findings highlight a context dependent, tumor-promoting role of ACACA inhibition and underscore the need for combinational strategies to avoid potential adverse outcomes in metabolic therapies. Trial registration Not applicable. Graphical Abstract